(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
In this experiment, an experiment was conducted on 54 three-month-old white mongrel rats. The experiment was carried out after the animals were fixed on wheeled vehicles, during the experiments, when the vehicle accelerated, when the required speed was reached, the vehicle, together with the animal, hit the wooden barrier with the frontal part. In this way, an imitation of a traffic accident was carried out, which caused craniocerebral trauma of varying severity in animals. The vehicle at the same time developed a speed of about 8 km per hour. The animals participating in the experiment, one by one, passed through the Morris water maze, for the analysis of their ability to remember after the injury.